NOVEL MICRO-SCALE TECHNIQUES TO ESTABLISH A LIFE-CYCLE ANALYSIS OF EARTHEN-BUILT STRUCTURES IN SCOTLAND, UK - Adderley, Paul; Parkin, Simon; McLaughlin, Dorothy; Kennedy, Craig (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The rapid changes in climate predicted for the 21st century presents a clear threat to the continued conservation and maintenance of historic vernacular buildings constructed with earth materials. With custodians of such vernacular heritage requiring a strong evidence base in order to prioritize the maintenance of such fabrics, it is clear that experimental studies considering the decay of earth materials corr elated to t heir provenance or l ifecycle in futur e environments is r equired. This paper reports on a set of scientiic initiatives designed to facilitate an evidence-based proactive approach, rather than an anecdotal and reactive approach, to the future repair and maintenance of such structures. Since climate change is manifested in different ways according to geographic location, process-led understandings are paramount. Two major techniques are used. First, thin-section micromorphology is an established technique for analysis of microscopic-structural features, as well as more extensive matrices of soils. It allows spatially-related observations to be linked to physical and chemical measurements at scales relevant to exchange processes in these materials. Second, a novel form of luminescence dating, allowing rapid on-site relative chronologies to be established, has been developed to permit temporal aspects and, hence, rates of change in the structures’ lifecycle to be determined. Using these techniques to analyze the wide range of constructional materials across a variety of regional environmental contexts in Scotland allows a multi-way comparative analysis. Sites considered include the dry internal structures of a stone-clad 18thcentury merchant’s house in Brechin, Angus; water-saturated earth-inill of wall from a house in Leetown, Perthshire, and exterior walling materials rich in cereal husks taken from Fladdabister, Shetland. Preliminary indings show differences in composition, internal matrix features, and relative age of these materials. This provides the basis for lifecycle analysis of these materials to be outlined in r elation to cl imatically-related factors.